Gadflies in the public space : a Socratic legacy of philosophical dissent - Jahanbegloo, Ramin (Lexington Books, 2017)
This book suggests a link between the citizen-philosopher Socrates and the radical, disobedient, and nonviolent Socrates. Ramin Jahanbegloo explains how these two complementary characteristics were transmitted to nonviolent reformers and practitioners Henry David Thoreau, Mahatma Gandhi, Martin Luther King Jr., and Albert Camus.